2016
DOI: 10.1080/19443994.2015.1040465
|View full text |Cite
|
Sign up to set email alerts
|

Adsorptive removal of Cr(VI) from aqueous solutions with an effective adsorbent: cross-linked chitosan/montmorillonite nanocomposites in the presence of hydroxy-aluminum oligomeric cations

Abstract: 2015):Adsorptive removal of Cr(VI) from aqueous solutions with an effective adsorbent: cross-linked chitosan/montmorillonite nanocomposites in the presence of hydroxy-aluminum oligomeric cations, Desalination and Water Treatment, A B S T R A C TOn the basis of laboratory research, the adsorbent of cross-linked chitosan/Al 13 -pillared montmorillonite (CCPM) was examined on the removal of Cr(VI) from aqueous solutions. In order to determine the effects of process parameters namely cross-linked chitosan-to-clay … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The chromium adsorption was described by Langmuir isotherm and intraparticle diffusion model. Wang et al [41] prepared chitosan-Al-pillared montmorillonite nanocomposite to remove Cr(VI). They reported that the maximum adsorption capacity of chromium was 15.68 mg/g for pH 6.38 and ambient temperature.…”
Section: Discussionmentioning
confidence: 99%
“…The chromium adsorption was described by Langmuir isotherm and intraparticle diffusion model. Wang et al [41] prepared chitosan-Al-pillared montmorillonite nanocomposite to remove Cr(VI). They reported that the maximum adsorption capacity of chromium was 15.68 mg/g for pH 6.38 and ambient temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Efforts have been conducted to remove the toxic heavy metals from water using clay as the support and chitosan as the polymer [ 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 ]. Divalent copper ions were removed from water using chitosan–silver NPs clay composite with a maximum adsorption capacity (181.6 mg/g) at pH 7 [ 94 ].…”
Section: Clay-polymers Nanocomposites For Pollutants Removalmentioning
confidence: 99%
“…In the same context, Chitosan–Al-pillared montmorillonite nanocomposite was used to remove Cr (VI) with an adsorption capacity of 15.68 mg/g [ 97 ]. Lead and copper divalent ions were removed with a similar nanocomposite prepared with clay: chitosan ratio of 1:0.45 to remove Pb (II) and Cu (II) at pH 6.5 with an efficiency of 99.5% and 96%, respectively via chemisorption mechanism.…”
Section: Clay-polymers Nanocomposites For Pollutants Removalmentioning
confidence: 99%